Global monitoring report 2010 the MDGs after the crisis. (Washington, D.C. : World Bank, 2010)
The book examines the impact of the worst recession since the Great Depression on poverty and human development outcomes in developing countries.
Includes bibliographical references.
nif 23/04/13, ijb 21/02/2019
Loans
Keywords: Economic assistance; Financial crises; Developing countries; Developing countries